TECTONIC SETTING AND DEFORMATION OF THE KALLIDROMO MT, CENTRAL GREECE - Migiros, G.; Antoniou, Vas.; Papanikolaou, I.; Antoniou, Var. (Bulletin of the Geological Society of Greece, 2010)
Kallidromo Mt. consists of alpine formations which in places are unconformably covered by Neogene and Quaternary sediments. The ophiolites are overthrusted on the massive Mesozoic platform carbonate sequence, which forms the basement unit. The base of the tectonic nappe is characterized by a tectonic melange that consists of sandstones, clay stones, limestones, cherts and basaltic rocks that are mainly observed in pillow forms. Two distinct compressional deformation phases (D1, D2) are traced. Deformation D1 whereas the fold axes, the predominant schistocity planes and shear zones clearly follow a N295o (±10o )-115o (±10o ) trend that relates to the Upper Jurrasic-Lower Cretaceous ophiolitic emplacement of the Eo-alpine orogeny and is the predominant feature over the entire study area. Deformation D2 relates to the Cretaceous-Eocene alpine orogeny, follows a N020o (±15o )-N200o (±15o ) trend and has a much weaker and secondary imprint in the study area. The tectonic study of the alpine and post-alpine formations shows a complex deformation pattern with a variety of quantitative and qualitative characteristics. These variations can be correlated with different phases and stages of deformation (compressional to extensional) from the timing of the tectonic emplacement of the ophiolites inUpperJurrasic-Lower Cretaceous up to the present-day field.